Methods of Forage Moisture Testing - Marcelo Wallau; Joao Vendramini (EDIS)
Determining forage moisture is an essential procedure for estimating forage mass in pastures, determining harvesting or baling point for preserved forages, and calculating dry matter of feedstuff for total mixed rations. This 3-page document discusses methods and pieces of equipment available to estimate forage moisture. Written by M. Wallau and J. Vendramini, and published by the UF/IFAS Agronomy Department, revised June 2019. http://edis.ifas.ufl.edu/ag181